ON PROCEDURAL SEMANTICS OF STRONG TYPED FUNCTIONAL PROGRAMS - Hakopian, R. Yu. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
The paper is devoted to procedural semantics of strong typed functional programs that are based on interpretation algorithms. These algorithms use three operations: substitution, one-step β-reduction and one-step δ-reduction. It is proved that the procedural semantics, based on any of such algorithms are consistent. It is also proved that procedural semantics, based on sevеral interpretation algorithms are incomparable.